Implantación de un sistema contable por órdenes de producción para la carpintería del señor segundo José Félix Maldonado arias de la ciudad de Loja periodo octubre a diciembre del 2014 - Pinzón Carrión, Luisa María (2015)
Cost accounting is very important in industrial enterprises or processing of raw materials, as these constitute an information system that categorizes, collects, controls and allocates costs to facilitate decision making, planning And anagement control. The implementation of an accounting system for production orders; is performed based on the overall objective Implement an accounting system for production orders for carpentry Mr. José Felix Maldonado Arias second city of Loja period October to December 2014 General, which met the following specific objectives are broken down in the process of implementing the accounting system, which began with: Plan and prepare a manual accounts with description; design records of production activities (process costs for production orders); make the accounting process and a determine the financial statements. Similarly to comply with the same methods and techniques with empirical criteria, allowing the owner to have information about the unit and total cost of their products were applied, since that has not stock cards, nor is there control of entry and exit of materials; Similarly, it is not considered in Its entiretyin directmanu facturing costs. Having completed this study concluded that for better financial management of the business research recommends allocating costs taking into account the raw material, labor and manufacturing overhead costs, use cards transcript, as well as making opening a current account that is used exclusively for business.